Analysis of Road Damage Using the Bina Marga Method on the Lamongan City - Mojokerto Border Road Section - Mashudi, Anang; Muhammadun, Haris; Marleno, Risma (CV. Proaksara Global Transeduka, 2024)
Road as an important facility for the community to achieve a desired goal both mobilizing goods and services. On the Lamongan City – Mojokerto Regency Border Road Section of STA 20+000 - 26+000 based on the field has experienced a decrease in road services that are not stable / comfortable with a lot of damage to the road. This study aims to determine the priority order value of road surface damage based on the Bina Marga method, determine the handling of road maintenance and the cost of handling road maintenance based on the two methods. From the results of the research, the priority order value of road damage on the Lamongan City - Mojokerto Border Road Section of STA 20+000 - 26+000 with the Bina Marga method is the priority order value of road damage 5.5, this includes a periodic maintenance handling program, the cost of handling road maintenance with the Bina Marga method is Rp. 9,479,663,479.46.